Development and Validation of an Autonomy Questionnaire for Chinese Adolescents From the Perspective of Network Culture - Li, Yi; Chen, Hong; Zheng, Yue-li; Wu, Ling-ling; Fan, Cui-ying (Frontiers in Psychology, 2022)
This study developed a measure of autonomy for adolescents in contemporary China. First, data from 44 interviewees—40 secondary school students, 2 parents, and 2 secondary school teachers—were used to explore the connotation and theoretical structure of autonomy in adolescents in China. Next, a preliminary Adolescent Autonomy Questionnaire was created from the interview data and administered to 775 secondary school students. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to verify the factor structure. Lastly, 614 secondary school students completed the Adolescent Autonomy Questionnaire, Personal Growth Initiative Scale-II, and Adolescence Ego Identity Crisis Scale to evaluate criterion validity. The final version of the Adolescent Autonomy Questionnaire included 16 items and 4 subscales: autonomous decision-making, autonomous regulation, autonomous protection, and autonomous problem-solving. The total variation of the cumulative interpretation questionnaire was 62.54%. The CFA results showed that the four-factor model fit the data well: χ2/df = 2.340, CFI = 0.949, RMSEA = 0.042, SRMR = 0.046. Evaluation of the psychometric properties of the Adolescent Autonomy Questionnaire provided support for the reliability and validity of the measure. Thus, it serves as an effective measurement tool for assessing the autonomy of adolescents in China.